The Environment Review 2012 - CURTIS, JOHN A. (ESRI)
The Environment Review 2012 presents projections of environmental emissions covering the period to 2030. The projections, which are based on current policies, provide a baseline of projected emissions (e.g. greenhouse gases, waste generation) to which the effects of any new policy can be compared. We highlight areas where government intervention, in addition to current policies, is required to meet committed targets and avoid environmental damage, concentrating on the areas of greenhouse gas emissions, the expansion of agricultural output and waste management. The projections presented in this report are based on a series of environmental and economic models. Ireland?s Sustainable development model (ISus) was used to develop environmental emissions projections. ISus is a simulation model that combines behavioural equations to predict future levels of environmental emissions. The current version of the model uses data for the period 1990-2009/10 for calibration and to estimate behavioural relationships, while projections are generated for the period 2010/11-2030. ISus covers a range of potential pollutants (to air, water and waste) emanating from 20 sectors of the economy, including the residential sector. Underlying the environmental figures are a number of model projections on population growth, domestic and international economic growth, energy and carbon markets. The most important of these is the scenario developed using the ESRI?s macroeconomic model, HERMES. This provided the economic data upon which the ISus emissions projections are based. Medium-term economic projections in the current period of uncertainty in the euro area are fraught with difficulty. Though subject to considerable uncertainty we present emissions based on just one economic projection. That underlying economic scenario may be overly optimistic, especially in the short term; for instance it is much more favourable on the short term outlook than the ESRI?s Quarterly Economic Commentary. Regardless of timing, a growing population and an expanding economy, when recovery firmly takes hold, will potentially lead to growing pressure on the environment through increased emissions and waste generation once the EU economy recovers; and the purpose of this report is to highlight where these environmental pressures are likely to arise.
PUBLISHED
Keywords: Environment; Waste Management; Water Quality; Renewable Energy; Greenhouse Gas